2005
DOI: 10.1007/s00442-005-0161-x
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope analyses provide new insights into ecological plasticity in a mixohaline population of European eel

Abstract: Recent studies have shown that anguillid eel populations in habitats spanning the marine-freshwater ecotone can display extreme plasticity in the range of catadromy expressed by individual fishes. Carbon and nitrogen stable isotope analysis was used to differentiate between European eels (Anguilla anguilla) collected along a short (2 km) salinity gradient ranging from <1 per thousand to approximately 30 per thousand in Lough Ahalia, a tidal Atlantic lake system. Significant differences were recorded in mean de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(131 citation statements)
references
References 75 publications
(94 reference statements)
5
125
0
1
Order By: Relevance
“…Ontogenetic trophic shifts have been observed in a wide range of marine mammals and Wsh (e.g. Olson 1996;Harrod et al 2005;KnoV et al 2008), but the existence of such dietary changes within gelatinous species is not well documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ontogenetic trophic shifts have been observed in a wide range of marine mammals and Wsh (e.g. Olson 1996;Harrod et al 2005;KnoV et al 2008), but the existence of such dietary changes within gelatinous species is not well documented.…”
Section: Discussionmentioning
confidence: 99%
“…SIA provides a useful tool for examining ontogenetic dietary shifts in a range of consumers (e.g. Olson 1996;Harrod et al 2005;KnoV et al 2008); however, such patterns have not been examined in jellyWsh. If preservation eVects exist, and are not constant across a gradient of consumer body size, this may aVect our capacity to correctly interpret information regarding trophic ecology from isotope data based on preserved samples.…”
Section: Introductionmentioning
confidence: 99%
“…15 N values varied largely (5.2-12.6 ‰) among the mesopelagic species, and positive enrichment with body length was observed within species such as longneck eel (KUB: r = 0.976, p > 0.1), 236 Harrod et al (2005) found much more depleted δ 13 C values (-23.6 ‰ average) in European eels (> 30cm in body length) collected in the freshwater habitat than those in the marine habitat (-16.3 ‰ average). Likewise, Bardonnet & Riera (2005) observed a significant shift of isotopic signatures from marine glass eels to river pigmented eels, where the pigmented eels, after starting to assimilate terrigenous organic matter sources, were observed to have lower δ 13 C (-26.7 to -22.7 ‰) than the marine glass eels (-21.4 ± 0.3 ‰).…”
Section: Stable Isotope Ratios Of Mesopelagic Fishesmentioning
confidence: 98%
“…Las especies catádromas son aquellas que inician su ciclo de vida en el mar, desde donde luego migran a cursos de agua dulce para crecer y desarrollarse, y cuando alcanzan su madurez sexual, regresan a las aguas marinas de origen, para completar su proceso reproductivo, como la anguila. Harrod, et al (2005) estudiaron la plasticidad ecológica de la anguila europea (Anguilla anguilla) en una gradiente de salinidades de 1-30 g/l en el lago Ahalia (oeste de Irlanda). Encontraron tres grupos de anguilas en función de las señales isotópi-cas medidas (δ 15 N y δ 13 C), las de agua dulce, las de agua salobre y las marinas.…”
Section: Implicaciones Ecológicas De Las Migraciones De Pecesunclassified